Recognize Number of fingers from Single hand gesture Image using Image processing and Neural Network - Bhavsar, H; Trivedi, J (International Journal of Computer Sciences and Engineering, 2025)
Objective of proposed research is to recognize total number of fingers from hand gesture image. This kind of system is very useful for mute people who can communicate through computer with others. This research paper defines proposed methodology for recognition of total fingers from hand gesture image. Images are processed by various image processing functions in MATLAB 2018. After extraction of features, finally recognition is done through Neural Network classification algorithm. For testing, 100 different images of hand gesture have taken from different people. Average result accuracy is 92%.